Study of the Impact of Worm Shaped Honing Wheel on Gear Honing Speed - Liu Chang; Lin Jiachun; Yu Bo (Jixie chuandong)
The gear after honing has many advantages,such as good tooth surface texture,smaller noise in transmission,high residual compressive stress and long lifetime etc. In the gear honing process,the relative speed which is between honing wheel and processing tooth surface determines honing process capacity and tooth texture. From the theory model of involute helicoid,the relative velocity formula at contact points when worm honing wheel and work piece are engaging is derived. By analyzing the change trend of relative velocity at contact points,the parameters of worm honing wheel which related to the change of velocity are found. According to adjustment of the parameters of number of thread and reference circle,the influence on the relative velocity is analyzed,then optimizing design of worm honing wheel is carried out.